2018
DOI: 10.2147/ppa.s161151
|View full text |Cite
|
Sign up to set email alerts
|

Primary nonadherence to chronic disease medications: a meta-analysis

Abstract: BackgroundMedication nonadherence is a global problem that requires urgent attention. Primary nonadherence occurs when a patient consults with a medical doctor, receives a referral for medical therapy but never fills the first dispensation for the prescription medication. Nonadherence to chronic disease medications costs the USA ~$290 billion (USD) every year in avoidable health care costs. In Canada, it is estimated that 5.4% of all hospitalizations are due to medication nonadherence.ObjectivesThe objective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(85 citation statements)
references
References 44 publications
7
73
0
5
Order By: Relevance
“…Our finding is consistent with a recent study in the US, where a PMN prevalence of 18% was reported in 32 586 patients aged ≥65 years with new prescriptions for their chronic disease. However, a review by Lemstra et al reported a lower overall PMN rate of 14.6% . We postulate two reasons that could have resulted in this difference.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Our finding is consistent with a recent study in the US, where a PMN prevalence of 18% was reported in 32 586 patients aged ≥65 years with new prescriptions for their chronic disease. However, a review by Lemstra et al reported a lower overall PMN rate of 14.6% . We postulate two reasons that could have resulted in this difference.…”
Section: Discussionmentioning
confidence: 68%
“…In view of the significance of PMN, there is a need to determine its prevalence and associated factors in different chronic diseases. A recent systematic review and meta‐analysis reported an overall PMN rate of 14.6% across four chronic diseases, namely hypertension, hyperlipidaemia, diabetes mellitus and depression . The review included 24 studies, of which four were randomised controlled trials.…”
Section: Introductionmentioning
confidence: 99%
“…Nonadherence is one area where mHealth may have the most potential to positively impact patient care [25]. It is well established that nonadherence is common among patients managing chronic medical conditions and takes many forms [26]. Patients with poorly controlled asthma often do not use their controller medications consistently or with the proper inhaler technique [27].…”
Section: Adherence Systemsmentioning
confidence: 99%
“…To start, it is important to define medication nonadherence. Adherence is described by WHO as “the extent to which a person's behaviour—taking medication, following a diet, and/or executing lifestyle changes, corresponds with agreed recommendations from a healthcare provider.” 1 Primary nonadherence is the rate at which the patient fails to fill their medications after having been prescribed by a provider 2 . Primary nonadherence rates in adults with asthma are estimated at 14 to 40% 3 .…”
Section: Characterizing Medication Nonadherence In Asthmamentioning
confidence: 99%
“…1 Primary nonadherence is the rate at which the patient fails to fill their medications after having been prescribed by a provider. 2 Primary nonadherence rates in adults with asthma are estimated at 14 to 40%. 3 For those patients who take the step of filling their medication and having it in their homes, secondary nonadherence rates can be measured.…”
Section: Characterizing Medication Nonadherence In Asthmamentioning
confidence: 99%